Seasonality in the Emission of Contact Calls in Spix's Disc-Winged Bats (Thyroptera tricolor) Suggests a Potential Role in Mate Attraction - Hernández Pinsón, Héctor Andrés (2022)
Multiple studies show that animals exhibit consistent individual differences in behavior, but they also experience short-term changes in their behavioral responses associated with seasonal events, most notably reproduction. We compare calling rates between the breeding and non-breeding seasons, and between males and females, in Spix’s disk-winged bats (Thyroptera tricolor). This species performs an exchange of inquiry and response calls in a context of social coordination and these vocalizations are used by individuals to signal roost location. Our results indicate that during the breeding season all males vocalize and also emit a greater number of response calls. In females, we found that there is no significant difference in their vocal behavior during the breeding and non-breeding seasons. Even though being vocal leads to greater energy costs and risk of predation, males were more vocal and emitted more vocalizations when females are known to be ovulating. Therefore, our results suggest that response calls may not only facilitate group cohesion, as found in previous studies, but that it may also play a role in courtship.